Correlation between mentors’ communication in e-mentoring, mentees’ self-efficacy and mentees’ academic performance: evidence from a Malaysian Public Research University - Ismail, Azman; Arshad, Mohd Mursyid; Samsudin, Asyakireen; Mohamad, Nur Izzaty; Omar, Najihah (Blue Eyes Intelligence Engineering and Sciences Publication, 2020)
E-mentoring is often viewed as an informal teaching and learning method in excellent higher education institutions. Recent studies highlight that well-designed e-mentoring programs will not be able to support their objectives if mentors do not have capabilities to communicate effectively in the mentoring system. Even though this relationship has widely been examined, the role of mentors’ communication in e-mentoring as a significant determinant is not adequately discussed in the higher education institution literature. Thus, this study was done to assess the correlation between mentors’ communication in e-mentoring, mentees’ self-efficacy and mentees’ academic performance. A survey method was utilized to collect data from students at a public research university in Malaysia. The outcomes of the Statistical Package for Social Science displayed that the competency of mentors to openly deliver mentoring information through technology media had strongly invoked mentees’ self-efficacy. As a result, this situation could lead to an enhanced mentees’ academic performance in the examined higher education institution.